The social and psychological problems for divorce phenomenon and how to be solved (Journal of Human Sciences, 2021)
As a result of crisis in Libya there are some social Issues related to war and the changes those happened in all around country , one of these Issues   has become a real  threat to a family as  a strong foundation , that threat is increasing of divorce cases , and according to official statistics in the partial court in  sebha  there are so great rate of divorce cases from 2000 to 2019 , so these cases of divorce Cause many problems social and psychological , all the members of the family suffer of these. problems because the family  is The basic nucleus of society If  it is reformed, society is reformed, and if it is corrupted, society is corrupted. The study problem has been formulated into one main question : what are the most important social and psychological problems Caused by divorce and what are the ways those help in reduce  the divorce cases. Descriptive method is used in this study  which is the one of important methods , who contributes to determine the problem of study  , And interprets all surrounding conditions about the problem, At the end of this study there are some consequences has been extracted , one of these consequences that the divorce is one of the most dangerous problems which is effect  the family In particular and the society generally.